Determination of locations of high wall stresses in an abdominal aortic aneurysm using computer simulation - Marañon Jr., Dioscoro P.
From a biomechanical point of view the possible locations of rupture in an abdominal aortic aneurysm (AAA) could be those points which experiences high wall stresses. If these locations of rupture can be identified before they fail and couse death, proper surgical intervention can be made and possibly save lives. At present there is still no fixed method in determining where and when rupture will occur in an AAA. This study presents a developmental alternative mechanism and attempts to tackle the problem by using images from Computer Tomography (CT) scans of a patient, which when converted to solid models using the 3-D soid modeling software can then be anlyzed using Finite Element Analysis (FEA). As a first approximation solid models were smoothened by reducing the number of traced points to eliminate excessive curvature, and uniform thickness was assumed for the shell. Material properties such as modulus of elasticity and Poisson's ratio were taken from previous experimental studies. For this initial study, the AAA tissue was assumed to be linear, elastic, isotropic and thin-walled shell. An internal, constant end-systolic pressure was applied to the shell. Both ends of the AAA tissue were constrained in the axial direction, and structural static type of analysis was employed. The von-Mises stresses and displacements were solved at different parts of the AAA tissue using finite element method. Previous studies focused on factors that cause such as diameter of bulge, asymmetry, volume, degree of curvature, high stresses, surface geometry, degree of twist, and inflection points. The results of this study showed that combined factors of thickness, internal pressure, concavity factor, strain or degree of expansion, twist and bending due to geometry need to be consider in determining the possible locations of rupture in an AAA. The framework presented in this study can possibly be initially used in monitoring of patients with AAA.